2020
DOI: 10.3238/arztebl.2020.0480
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracranial Hypotension

Abstract: pontaneous intracranial hypotension was first described in 1938 by Georges Schaltenbrand, a neurologist in Würzburg, Germany, who named it "hypoliquorrhea" (1, 2). Isolated case reports appeared in the 1940s, and the syndrome has been described many times in print since the mid-1990s (3-9).* Schievink et al. carried out an observational study in the greater Los Angeles area to determine the incidence of SIH. 11 patients with SIH and 23 with spontaneous subarachnoid hemorrhage (SAH) were seen in an emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 37 publications
0
48
0
7
Order By: Relevance
“…It is now well-recognized that spontaneous intracranial hypotension (SIH) is an important cause of new-onset daily headaches, particularly in young and middle-aged individuals (16). An orthostatic headache, i.e., a headache that is exacerbated by the upright position, is the prototypical manifestation of SIH, but the positional component often becomes less recognizable with the passage of time (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well-recognized that spontaneous intracranial hypotension (SIH) is an important cause of new-onset daily headaches, particularly in young and middle-aged individuals (16). An orthostatic headache, i.e., a headache that is exacerbated by the upright position, is the prototypical manifestation of SIH, but the positional component often becomes less recognizable with the passage of time (16).…”
Section: Introductionmentioning
confidence: 99%
“…It is now well-recognized that spontaneous intracranial hypotension (SIH) is an important cause of new-onset daily headaches, particularly in young and middle-aged individuals (16). An orthostatic headache, i.e., a headache that is exacerbated by the upright position, is the prototypical manifestation of SIH, but the positional component often becomes less recognizable with the passage of time (16). Spontaneous intracranial hypotension may also cause various other more or less serious neurologic manifestations such as hearing loss, dizziness, diplopia, nuchal rigidity, coma, and bibrachial amyotrophy (16).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed the feasibility of an automated approach of classifying head MRI scans to identify patients with spontaneous intracranial hypotension (SIH). A single MRI sequence, namely a contrast-enhanced T1-weighted MPRAGE sequence, which is part of our standard MRI protocol was analyzed [ 11 ]. As the segmentation of the considered volumes (superior sagittal sinus, both transverse sinuses, suprasellar cistern) is done by a computer there is no variability between raters allowing for an objective and unbiassed MRI assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The goal is to locate the ventral dural tear by exactly locating the point of egress of iodinated contrast medium into the epidural space. This is achieved with the iodinated contrast medium slowing flowing into a caudo-cranial direction on the ventral side of the subarachnoid space [25][26][27] (Fig. 2).…”
Section: Spine Mrimentioning
confidence: 99%